Ceropegia ornata (Asclepiadoideae, Ceropegieae) a new species from Eastern Cape, South Africa - Martínez-Azorín, Mario; Dold, Anthony P.; Powell, Michael John (Phytotaxa, 2025)
A new species of Ceropegia, named C. ornata, is described from the Albany Thicket Biome in the Eastern Cape Province of South Africa. Under the traditional generic concepts, the new species would belong to Brachystelma based on its open-rotate flowers and flattened tuber. However, following the recently enlarged concept of Ceropegia s.l., which includes Brachystelma and the stapeliads, we provisionally place the new species in Ceropegia s.l. Ceropegia ornata is morphologically closest to C. delicata (≡ Brachystelma delicatum) but differs in several reproductive and vegetative characters, such as shorter stems, smaller leaves, different corolla colouration, and distinct corona structure. Ceropegia ornata may also be confused with the more distantly related C. huttonii (≡ B. huttonii) and differences to this species are discussed as well. A complete description is presented for the new species, and illustrations of all three species under discussion are provided.